Social Cohesion Strengthens Social Ties among University Students in Malaysia - Kamri, Khairol Anuar; Hamid, Aizathul Hani Abd; Zan, Ummi Munirah Syuhada Mohamad; Abdullah, Azlina; Jalil, Faridah; Noor, Mansor Mohd (South Asian Journal of Social Sciences and Humanities, 2021)
The pattern of ethnic relations and religion among university students is always the focus of understanding Malaysian unity and ethnic relation. This study explores the study of unity by  recalling the concept of solidarity put forward by Durkheim. Unity as the main concept needs  to be reinterpreted by studying the social realities and social history in Malaysia. Unity happens in the long life of harmony since the 1969 ethnic riots until now, but Malaysia still faces social  tensions and fights between ethnic and religious in society. Unity is still considered fragile and  just a dream. The concept of social cohesion is expressed as a social phenomenon that needs to  be studied as the atmosphere is harmonious but colored with social tension. The multi-culture  of Malaysian come from its relationship with east civilization before pre-colonial and the  British colonization. The differences between ethnicity and religion in social order cause  tension and conflict among the groups. Yet development in the last four decades has changed  the social landscape where multi-ethnic societies have turned into a socially diverse society.  University students are targeted as respondents in understanding the concepts and patterns of  social cohesion among them. Studies show that social cohesion among students is developed. The dimension and item analysis show that there are ethnic and religious differences, but the  differences are relatively small. It is suggested that follow-up studies in identifying the form  and understanding of the relationship of social cohesion on campus should be conducted through qualitative and ethnographic research design in obtaining data to strengthen ethnic  relations in the university. Input from this follow-up study finding will strengthen social  cohesion among students that can help governance and university development is well  managed by identifying the social gap.
Keywords: Unity; Social Cohesion; Ethnicity; Colonial Science